2020
DOI: 10.21203/rs.3.rs-55459/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of APOE ε4 genotype on amyloid-β and tau accumulation in Alzheimer’s disease

Abstract: Background: To assess the effects of apolipoprotein E (ApoE) ε4 genotype on amyloid-β (Aβ) and tau burden and their longitudinal changes in Alzheimer’s disease (AD) spectrum.Methods: Among 272 individuals who underwent PET scans (18F-florbetaben for Aβ and 18F-flortaucipir for tau) and ApoE genotyping, 187 individuals completed 2-year follow-up PET scans. After correcting for the partial-volume effect, we compared the standardized uptake value ratio (SUVR) for Aβ and tau burden between the ε4+ and ε4- groups. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Accumulation of protein Tau is also likely to play a role as a study showed an increase of tau PET uptake in the entorhinal cortex and hippocampus among ε4carriers independently of Aβ load [37]. Poorer cognition has been related to tau PET accumulation, even among Aβ-negative ε4 carriers [38], suggesting that the APOE ε4 allele may enhance the vulnerability to progressive tau accumulation in the AD spectrum [39].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of protein Tau is also likely to play a role as a study showed an increase of tau PET uptake in the entorhinal cortex and hippocampus among ε4carriers independently of Aβ load [37]. Poorer cognition has been related to tau PET accumulation, even among Aβ-negative ε4 carriers [38], suggesting that the APOE ε4 allele may enhance the vulnerability to progressive tau accumulation in the AD spectrum [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in PET studies among asymptomatic APOE ε4 carriers, the largest correlation between the cerebral metabolic rate for glucose and APOE ε4 status was noted in the parietotemporal regions of the brain [ 37 ]. The parietotemporal cortex was noted as having the highest degree of tau accumulation on 8 F-flortaucipir PET among APOE ε4 carriers compared to non-carriers regardless of the amyloid positive status [ 38 ]. Even though the specific mechanism of this parietotemporal vulnerability is unclear, one could speculate that regional neuronal energy metabolism vulnerabilities not unlike the posterior cingulate in AD are possible leading to early regional synaptic loss [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy might be due to differences in sample composition: although both studies assessed vascular risk with the Framingham 10-year CVD risk score, Rabin et al found a wider range (4% - 74%) of CVD risk in their sample compared to ours (4% - 51%). Additionally, their sample consists of a higher percentage of APOE e4 carriers (31% vs. 26%), who on average have been shown to have greater vascular risk (Mielke et al, 2011) and AD neuropathology (Baek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%